Crystal Structure of Human Protein Tyrosine Phosphatase SHP-1 in the Open Conformation - Wang, Wei (2011)
SHP-1 belongs to the family of non-receptor protein tyrosine phosphatases (PTPs) and generally acts as a negative regulator in a variety of cellular signaling pathways. Previously the crystal structures of the tail-truncated SHP-1 and SHP-2 revealed an autoinhibitory conformation. To understand the regulatory mechanism of SHP-1, we have determined the crystal structure of the full length SHP-1 at 3.1 Å. Although the tail was disordered in current structure, the huge conformational rearrangement of the N-SH2 domain and the incorporation of sulfate ions into the ligand-binding site of each domain indicate that the SHP-1 is in the open conformation. The N-SH2 domain in current structure is shifted away from the active site of the PTP domain to the other side of the C-SH2 domain, resulting in exposure of the active site. Meanwhile, the C-SH2 domain is twisted anticlockwise by about 110°. In addition, a set of new interactions between two SH2 domains and between the N-SH2 and the catalytic domains is identified, which could be responsible for the stabilization of SHP-1 in the open conformation. Based on the structural comparison, a model for the activation of SHP-1 is proposed.